A randomised non-comparative phase II trial of cixutumumab (IMC-A12) or ramucirumab (IMC-1121B) plus mitoxantrone and prednisone in men with metastatic docetaxel-pretreated castration-resistant prostate cancer. Issue 13 (September 2015) - Hussain, Maha; Rathkopf, Dana; Liu, Glenn; Armstrong, Andrew; Kelly, Wm. Kevin; Ferrari, Anna; Hainsworth, John; Joshi, Adarsh; Hozak, Rebecca R.; Yang, Ling; Schwartz, Jonathan D.; Higano, Celestia S.
Abstract Background Cixutumumab, a human monoclonal antibody (HuMAb), targets the insulin-like growth factor receptor. Ramucirumab is a recombinant HuMAb that binds to vascular endothelial growth factor receptor-2. A non-comparative randomised phase II study evaluated cixutumumab or ramucirumab plus mitoxantrone and prednisone (MP) in metastatic castration-resistant prostate cancer (mCRPC). Patients and methods Men with progressive mCRPC during or after docetaxel therapy received mitoxantrone 12 mg/m2 on day 1 and prednisone 5 mg twice daily and were randomised 1:1 to receive either cixutumumab or ramucirumab 6 mg/kg intravenously weekly in a 21-day cycle. Primary end-point was composite progression-free survival (cPFS). Secondary end-points included safety, response, radiographic progression-free survival (PFS) and overall survival (OS). Sample size was based on a 50% increase in median cPFS from 2.6 (MP) to 3.9 months (either combination). Results 132 men were treated (66 per arm). Median cPFS was 4.1 months (95% confidence interval (CI), 2.2–5.6) for cixutumumab and 6.7 months (95% CI, 4.5–8.3) for ramucirumab. Median time to radiographic progression was 7.5 months for cixutumumab and 10.2 months for ramucirumab, with a median OS of 10.8 and 13.0 months, respectively. Fatigue was the most frequent adverse event (AE). Incidence of most non-haematologic grade 3–4 AEs was <10% on both arms. Grade 3 cardiac dysfunction occurred in 7.6% of patients on ramucirumab. Conclusion Combinations of cixutumumab or ramucirumab plus MP were feasible and associated with moderate toxicities in docetaxel-pretreated men with mCRPC. Of the two regimens, the ramucirumab regimen is worthy of further testing based on the observed cPFS relative to the historical control.